Combined bearing capacity of bucket foundations in soft-over-stiff clay - Xia, Huxi; Zhou, Mi; Niu, Fujun; Zhang, Xihong; Tian, Yinghui (Elsevier, 2022)
In this study, a series of three-dimensional small-strain analyses are carried out to explore the combined capacity of bucket foundations in soft-over-stiff clay under general loading. It aims to provide a supplement to existing design codes. Numerical models are generated and validated with existing data in open literature, where good agreements are obtained. The effects of the layered deposit are explored, including the thickness of the upper soft clay, the length of skirt, the magnitude of the vertical load, and soil properties. Due to the presence of soft clay, the uniaxial bearing capacities reduce significantly, reaching as low as 25% reduction compared to the caisson in uniform stiff clay. In the V-H, V-M and V-H-M spaces, the failure envelopes are normalized in unique shapes according to the geometry of the bucket. Based on the numerical results, an empirical design procedure is proposed to evaluate the failure envelopes of bucket foundations subjected to complex loading conditions in soft-over-stiff clay.